Some Results of Bondage Number of (n,k)-Star Graphs - Yunchao Wei; Hongxian Zhu; Junli Han (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In the computer network, bondage number is one of the most important parameters to measure the control theory of the computer network, denoted by b(G) for a network graph G. But predecessors have proved that computing them are very hard. So computing b(G) of some particular known gr-aphs is extremely valuable. In this paper, we determine b(Sn,2) and the precise lowerbound of b(G) of (n,k)-star graphs, denoted by Sn,k followed by some relative conclusions of n-star, denoted by Sn as the isomorphism of Sn,n-1. In addition, our method giving dominating set of Sn,k is easily understood, which presented a broadcast algorithm to determine dominating set of Sn,k. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3285